A NEW SUBGENUS AND A NEW SPECIES OF TRECHUS FROM ETHIOPIA (COLEOPTERA, CARABIDAE) - Vigna Taglianti, Augusto; Magrini, Paolo (Fragmenta entomologica, 2009)
In the present note Minitrechus, a new subgenus of Trechus, characterized in the 75 male by only the first tarsal segment dilated and dentate, and by much enlarged paramera, bearing three apical setae, clearly isolated from each other, is described. The new species, Trechus (Minitrechus) gypaeti, is light yellow in colour, rather flattened, with little eyes, pronotum not sinuate, with fore and hind angles blunt; third elytral stria with two discal setae. The median lobe of the aedeagus is short, stout, little arcuate, with a copulatory piece triangular, lanceolate and sharpened at the tip, little sclerified. Female gonostyli short and curved, bear a stout and long ensiform seta on the inner edge, flanked by two smaller ones.